Prompt release obligation in the jurisprudence of the International Tribunal for the Law of the Sea - Hamid, Abdul Ghafur@Khin Maung Sein (2011)
In accordance with Article 292 of the UNCLOS 1982, the International Tribunal for the Law of the Sea shall in its judgment determine in each case whether or not the allegation made by the applicant that the detaining State has not complied with a provision of the Convention for the prompt release of the vessel or the crew upon the posting of a reasonable bond or other financial security is well-founded. Because the 1982 Convention bestows extended jurisdiction on coastal States - a jurisdiction reaching far beyond the territorial seas - this new procedural safeguard of Article 292 is said to have been incorporated as a quid pro quo in order to safeguard the interests of the shipping nations. The present paper is an attempt to observe how Article 292 is in fact interpreted and applied by the ITLOS in the nine prompt release cases filed before it to date. The main thrust of the paper is to examine whether the overriding purpose of Article 292, that is, to serve as a compromise between the conflicting interests of the coastal and the flag states is fulfilled.